2018
DOI: 10.1093/nar/gky385
|View full text |Cite
|
Sign up to set email alerts
|

Cell penetrating thiazole peptides inhibit c-MYC expression via site-specific targeting of c-MYC G-quadruplex

Abstract: The structural differences among different G-quadruplexes provide an opportunity for site-specific targeting of a particular G-quadruplex structure. However, majority of G-quadruplex ligands described thus far show little selectivity among different G-quadruplexes. In this work, we delineate the design and synthesis of a crescent-shaped thiazole peptide that preferentially stabilizes c-MYC quadruplex over other promoter G-quadruplexes and inhibits c-MYC oncogene expression. Biophysical analysis such as Förster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 51 publications
(40 reference statements)
4
70
0
Order By: Relevance
“…Polyamides based on 2 and 3 repeating units of 2-aminothiazole-4-carboxylic acid were synthetized [69] and proved to bind selectively to c-MYC quadruplex over other G-quadruplex and duplex DNA and therefore inhibiting c-MYC oncogene transcription. Antiproliferative activity of the tripeptide was found in HeLa cells, caused by apoptotic pathway.…”
Section: Linear Peptidesmentioning
confidence: 99%
“…Polyamides based on 2 and 3 repeating units of 2-aminothiazole-4-carboxylic acid were synthetized [69] and proved to bind selectively to c-MYC quadruplex over other G-quadruplex and duplex DNA and therefore inhibiting c-MYC oncogene transcription. Antiproliferative activity of the tripeptide was found in HeLa cells, caused by apoptotic pathway.…”
Section: Linear Peptidesmentioning
confidence: 99%
“…resolved for transcription to occur. Compounds like enniantin-B, TH3, and APTO-253 that stabilize this structure decrease MYC transcription (44,45). Furthermore, efficient MYC gene transcription needs docking of BRD proteins and other co-activating molecules, including IKZF, NME2, and CDK9 at the promoter.…”
Section: Thematic Minireview: Myc-odc Axis In Cancermentioning
confidence: 99%
“…There have been efforts to develop ligands that will bind specifically to each G4 structure. Thiazole peptides were developed and tested for specific c-MYC G4 binding [64]. These experiments also showed that the ligand binds to c-MYC's G4 in slow exchange on the NMR timescale.…”
Section: G4-ligand Interactionmentioning
confidence: 99%